Expanded vaccination practice in 2-year-old children and maternal knowledge on expanded vaccination in Tien Giang, Vietnam - Nguyen, Giau Le Ngoc; Nguyen, Giang Vu Truong; Nguyen, Mai Thi Nhu; Nguyen, Doi Van; Phan, Ngoc Trung Thi; Tran, Van De; Pham, Trung Tin; Le, Minh Huu; Nguyen, Dat Tan; Pham, Tam Thi (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Vaccination plays a central role in protecting children against severe diseases and preventing child mortality. Objectives. This study aimed to determine the rate and factors associated with complete and timely vaccination in 2-year-old children, as well as maternal knowledge on expanded vaccination in Go Cong Tay district, Tien Giang province, Vietnam. Methods. A cross-sectional descriptive study was conducted on 558 2-year-old children and their mothers residing in Go Cong Tay district, Tien Giang province, Vietnam. The study employed a systematic random sampling method from June to September 2021. Results. The rate of complete vaccination in children was 74.7%. Factors associated with the rate of complete vaccination were occupation (OR=0.3; 95%CI: 0.1-0.7; p=0.006), economic status (OR=3.8; 95%CI: 1.7-8.6; p=0.001), and maternal general knowledge on expanded vaccination (OR=1.7; 95%CI: 1.1-2.6; p=0.01). The rate of timely vaccination was 47.8%. Factors associated with the rate of timely vaccination were maternal age group (OR=3.1; 95%CI: 1.6-6.0; p=0.001; OR=3.0; 95%CI: 1.3-6.6; p=0.006) and economic status (OR=0.4; 95%CI: 0.2-0.9; p=0.04). The rate of both complete and timely vaccination was 22.6%. Factors associated with the rate of complete and timely vaccination were maternal age group (OR=3.1; 95%CI: 1.3-7.2; p=0.009; OR=3.3; 95%CI: 1.2-9.1; p=0.02) and maternal general knowledge on expanded vaccination (OR=1.5; 95%CI: 1.02.4; p=0.03). The rate of maternal general knowledge on expanded vaccination was 57.5%. Conclusion. The rates of complete and timely vaccination are still low, and various factors influence expanded vaccination. Therefore, it is crucial to continue health education campaigns to improve knowledge on expanded vaccination, remind mothers of vaccination schedules, strengthen confidence in vaccination programs and vaccine safety, attract customers to vaccination services, provide adequate healthcare for children, and ensure vaccination activities during disease outbreaks.